Nutritional evaluation of chicken nuggets utilizing mungbean and rice flour - Maniago, Johnina T.
The effect on the nutritional value of chicken nuggets of the amount of mungbean and rice flour substituted for chicken was investigated. Moisture determination, crude fat, crude protein, ash, crude fiber and total dietary fiber determinations were conducted. Results showed that all samples contained low moisture and 1.54-2.40% ash. The sample with 62.5% chicken in the formulation was found to contain the highest amount of fat and fiber. Protein was highest in the sample with 31.2% chicken, 21.9% rice flour and 9.4% mungbean. Substitutions made played major roles in increasing the amount of protein in the samples.